Modeling Outcomes in Children With Biliary Atresia With Native Liver After 2 Years of Age. Issue 12 (3rd October 2020) - Venkat, Veena; Ng, Vicky L.; Magee, John C.; Ye, Wen; Hawthorne, Kieran; Harpavat, Sanjiv; Molleston, Jean P.; Murray, Karen F.; Wang, Kasper S.; Soufi, Nisreen; Bass, Lee M.; Alonso, Estella M.; et al.
Abstract : Approximately 50% of infants with biliary atresia (BA) undergoing Kasai portoenterostomy show survival with native liver (SNL) at age 2 years. Predictors of disease progression after age 2 years are unknown, despite estimates of 20%‐30% undergoing liver transplant (LT) between age 2 and 18 years. We sought to address this knowledge gap by developing prognostic models in participants of the multicenter prospective National Institutes of Health‐supported Childhood Liver Disease Research Network. We extracted 14 clinical and biochemical variables at age 2 years to develop two models for future outcomes: 1) LT or death (LTD) and 2) first sentinel event (SE), either new onset ascites, hepatopulmonary syndrome (HPS), or gastrointestinal (GI) bleed. A total of 240 participants, enrolled between 2004 and 2017, were followed until a median age of 5.1 years (range, 2.0‐13.3 years). Of these participants, 38 underwent LT (n = 37) or death (n = 1); cumulative incidence, 23.7% (95% confidence interval [CI], 16.2%‐32.0%). Twenty‐seven experienced either new‐onset ascites (n = 13), HPS (n = 1), or GI bleed (n = 14). One participant had ascites and GI bleed concurrently; cumulative incidence, 21.5% (95% CI, 14.2%‐29.8%) by age 10 years. The Cox proportional hazard model predicted risk of LTD, using total bilirubin, albumin, platelet count, and history of either ascites or cholangitis (BA LTD model), with a C‐index of 0.88 (range, 0.86‐0.89). A cause‐specific hazard competing risk model predicted SE using platelet count and gamma glutamyltransferase levels (BA SE model) with a C‐index of 0.81 (range, 0.80‐0.84). Internal model validity was assessed using Harrell's C‐index with cross‐validation. Conclusion: Stratification using these models identified risk of poor outcomes in patients with BA SNL after age 2 years. The models may identify those who would benefit from enhanced clinical surveillance and prioritization in clinical trials.